2017
DOI: 10.1177/1358863x17724221
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of statins on total mortality in abdominal aortic aneurysm (AAA) repair

Abstract: In this single center, retrospective cohort study we wished to compare early and total mortality for all patients treated for abdominal aortic aneurysms (AAA) with open surgery who were taking statins compared to those who were not. A cohort of 640 patients with AAA was treated with open surgery between 1999 and 2012. Patients were consecutively recruited from a source population of 390,000; 21.3% were female, and the median age was 73 years. The median follow-up was 3.93 years, with an interquartile range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Some related reports pointed out that calcium-channel blockers are associated with reduced aortic expansion and improved survival in AAD. [ 18 19 ] Calcium antagonists generally blocked the slow calcium channels, decreasing the influx of extracellular calcium,[ 20 ] which resulted in suppression of the sinoatrial and atrioventricular nodes,[ 21 ] vascular dilation with decreased blood pressure, and reduced cardiac contractility. Adequate blood pressure regulation and subsequent decreased pressure on the aortic wall through calcium-channel blockade may theoretically decrease risks of aortic enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Some related reports pointed out that calcium-channel blockers are associated with reduced aortic expansion and improved survival in AAD. [ 18 19 ] Calcium antagonists generally blocked the slow calcium channels, decreasing the influx of extracellular calcium,[ 20 ] which resulted in suppression of the sinoatrial and atrioventricular nodes,[ 21 ] vascular dilation with decreased blood pressure, and reduced cardiac contractility. Adequate blood pressure regulation and subsequent decreased pressure on the aortic wall through calcium-channel blockade may theoretically decrease risks of aortic enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Sven et al conducted a retrospective study in a single center to compare mortality for all AAA patients with open surgery and showed a significant beneficial effect of statin use on early and long-term survival. [13] Another study [14] also used ICD-9-CM codes to analyze the impact of preoperative statin use on the outcomes of Medicare patients who received either OPR or EVAR and showed mortality reduction at 90 days and 1 year. A systematic review and meta-analysis performed by Huang et al [8] also showed the benefit of statin therapy on survival after AAA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective cohort study reported that patients with AAA on statins treatment had a 38% reduction in long-term mortality after a medium follow-up of 3.93 years. 38 It is worthwhile for us to further evaluate the effectiveness of statin medication for AAA patients on the risk of developing AAA.…”
Section: Discussionmentioning
confidence: 99%